Arc lamps - Adamson, Edward E. (My University, 1905)
Introduction: In the opening years of the twentieth century, those taking a retrospective view of the nineteenth, predicted that marvelous indeed must be the advancement of the new century in electrical development if the high standard set IT the old is to be maintained. But every improvement paves the way and makes easier the path of the next, and the new century had scarcely begun until there came to those connected with electric lighting the announcement of a new arc lamb, the magnetitearc, whose efficiency is twice that of the most modern carbon lamps which, in their turn, are more efficient than any other artificial light. Volta for the first time in 1800 observed the phenomenon of heat and light caused by a current of electricity bridging a short gap in a broken circuit. As the luminous stream flowed between horizontal points, it arced upward because of the influence of the heated air and is, therefore, known as the "Voltaic Arc". Soon after, Sir Humphrey Davy obtained a four inch arc between points made from gas carbon. From that the carbon arc lamp has developed during the nineteenth century to be improved upon by the metal arc in the very first years of the twentieth. APPEARANCE. Whether or not the new arc has all the advantages claimed for it, the carbon arc has yet a long period of usefulness before it, if for no other reason than that it already occupies the arc lighting field. The carbon arc is much shorter than the metal arc because of the refractory nature of carbon. The arc is composed of a conductive bridge of volatilized material which composes the electrodes. The intense heat vaporizes most metals much easier than it does carbon and so the vapor bridge, in the case of metal electrodes, has the lower resistance both because of the larger amount of metal vapor present and the conductive nature of the material itself.
Citation: Adamson, Edward E. Arc lamps. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Arc Lighting; Modern Lamps; Light Standards; Photometer; Theses